Role of c-reactive protein in cardiovascular diseases - a review - MARY, D.ANGEL FASTINA; RANI. S, DR. LESLIE; DR. BRUNDHA M.P (The journal of contemporary issues in business and government, 2020)
Circulating level of C - reactive protein depicts the cardiovascular condition. By reviewing available studies, the current study determines that CRP level ( c- reactive protein level) within the upper quantile of the normal range constitutes an increased risk for cardiovascular events or diseases. CRP levels within the upper quartile/quintile of the traditional range indicates increased risk for cardiovascular events. High CRP levels in acute myocardial infarct after treatment shows an alarming sign. This is due to the response of the body to the inflamed atherosclerotic (coronary) vessels and adjacent myocardium. Localized CRP in infarcted myocardium activates the complement system, resulting in inflammation and thrombosis. After reviewing many literatures with correlation between CRP and cardiovascular disease, the current study explains the pathogenesis and its role in diagnosing myocardial infarction. The background of this current study may provide directions for prevention of cardiovascular events.